2021
DOI: 10.3390/medicina57050472
|View full text |Cite
|
Sign up to set email alerts
|

Psoas Muscle Index Defined by Computer Tomography Predicts the Presence of Postoperative Complications in Colorectal Cancer Surgery

Abstract: Background and Objectives: Sarcopenia is a recognized prognostic factor for both complications and survival in cancer patients. This study aims to analyze the relationship between sarcopenia measured by psoas muscle index on computer tomography scans and the presence of postoperative complications in colorectal cancer surgery. Materials and Methods: In a prospective study we recorded data from 51 patients who underwent colorectal cancer surgery in the Mures County Clinical Hospital, Romania. Total psoas muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
1
12
2
2
Order By: Relevance
“…Chai et al [10] revealed that sarcopenia de ned by TAMA was signi cantly associated with complications. Benedek et al [11] discovered that TPA was related to postoperative complications instead of PMD, consistent with Wu et al [9]. However, Pekařová et al [12] and Cuijpers et al [13] unveiled that PMD was correlated with postoperative complications rather than TPA.…”
Section: Introductionmentioning
confidence: 63%
“…Chai et al [10] revealed that sarcopenia de ned by TAMA was signi cantly associated with complications. Benedek et al [11] discovered that TPA was related to postoperative complications instead of PMD, consistent with Wu et al [9]. However, Pekařová et al [12] and Cuijpers et al [13] unveiled that PMD was correlated with postoperative complications rather than TPA.…”
Section: Introductionmentioning
confidence: 63%
“…A meta-analysis focused on patients undergoing esophageal cancer surgery found no correlation between sarcopenia and the rate of postoperative complications [8]. Recently, Benedek et al correlated the psoas muscle index as a continuous variable to the severity of postoperative complications in patients with colorectal cancer [19]. When examining the psoas index as a dichotomous variable, using distinct cut-off values, various authors proposed cut-off values linked to specific outcomes in diverse clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sarcopenia, this would have entailed comprehensive evaluations of skeletal muscle mass and function. Although CT imaging permits an estimation of total body skeletal muscle mass through visualization of major muscle groups, we lacked longitudinal imaging data for comparison (40)(41)(42)(43). Furthermore, muscle function tests such as grip strength were not routinely obtained for this cohort.…”
Section: Study Limitationsmentioning
confidence: 99%